Response to "A Comment on Vulnerability and Clientelism (2022)" - Gustavo J. Bobonis; Paul Gertler; Marco Gonzalez-Navarro; Simeon Nichter (Institute for Replication (I4R), 2023)
Bobonis, Gertler, Gonzalez-Navarro, and Nichter (2022) conducts a randomized control trial in rural Northeast Brazil designed to reduce the vulnerability of sampled households. In this development intervention, we constructed residential water cisterns across 425 neighborhood clusters in 40 municipalities, and examine effects using a longitudinal panel survey and electoral data at the precinct level. Ma, Monpetit, and Nordstrom's (2023) comment confirms the reproducibility of our results. Moreover, their comment does not challenge any of our article's primary findings: the cisterns treatment significantly r educed c itizens' vulnerability (Table 2), it decreased citizens' requests for private goods from politicians (Table 3), and it significantly decreased votes for incumbent mayors (Table 4). The comment by Ma, Monpetit, and Nordstrom (2023) discusses three aspects of robustness: (1) the matching of individuals in the panel over time, (2) how clientelist relationships are defined, a nd ( 3) t he c hoice of historical rainfall period. With regards to the first aspect, the comment reports some age inconsistencies across waves for a relatively small subsample, even though it states that results remain "stable in terms of both magnitude and statistical significance" when excluding these observations. As discussed below, our longitudinal rostering procedure accurately identifies i ndividuals a cross s urvey waves, though some minor measurement error exists in reported ages. With regards to the second aspect, the comment challenges Section VI of our article, which presents additional heterogeneity analyses in Table 5 to explore the role of clientelism in our primary results. More specifically, the comment argues that those results are not robust to a more restrictive coding of the binary clientelism marker employed to test heterogeneity. Contrary to their critique, we show that analyses in Table 5 of our article are indeed robust to a more restrictive coding. With regards to the third aspect, their comment indicates that halving the window of historical data used to normalize rainfall affects only a single, ancillary result: the cistern treatment's impact on one of three well-being measures we examine (Column 3 in Table 2). Since Ma, Monpetit, and Nordstrom (2023) indicate that "the overall message remains the same" - and it is not obvious that their approach is preferable - we do not discuss the third aspect below.
Keywords: 330